2017
DOI: 10.1016/j.jpsychores.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Increased psychiatric morbidity in women with complete androgen insensitivity syndrome or complete gonadal dysgenesis

Abstract: The increased psychiatric morbidity in women with CAIS and GD highlights the need for clinical awareness of the psychiatric vulnerability in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…In two studies (Chen et al, 2015;Rabkin et al, 2000), authors compared patients with their caregivers and one reported higher frequencies of both depressive and anxiety disorders in patients (Chen et al, 2015). In four out of eight comparisons with patients with non-rare diseases, patients with rare diseases showed higher rates than controls (Gündel et al, 2003;Huey et al, 2010;Jenkins-Jones et al, 2018;Mozzetta et al, 2008), two studies found no differences (Engberg et al, 2017;Ozel-Kizil, Akbostanci, Ozguven, & Atbasoglu, 2008), and in two studies, the authors reported higher frequencies in the comparison group (Dias et al, 2011;Moore et al, 2016).…”
Section: Comparisons With Control Groupsmentioning
confidence: 95%
See 2 more Smart Citations
“…In two studies (Chen et al, 2015;Rabkin et al, 2000), authors compared patients with their caregivers and one reported higher frequencies of both depressive and anxiety disorders in patients (Chen et al, 2015). In four out of eight comparisons with patients with non-rare diseases, patients with rare diseases showed higher rates than controls (Gündel et al, 2003;Huey et al, 2010;Jenkins-Jones et al, 2018;Mozzetta et al, 2008), two studies found no differences (Engberg et al, 2017;Ozel-Kizil, Akbostanci, Ozguven, & Atbasoglu, 2008), and in two studies, the authors reported higher frequencies in the comparison group (Dias et al, 2011;Moore et al, 2016).…”
Section: Comparisons With Control Groupsmentioning
confidence: 95%
“…A sensitivity analysis excluding two studies with a quality of <40% revealed a pooled prevalence of 18.8% (95% CI 13.8-25.2%). The prevalence of any lifetime affective disorder ranged between 11.6% (Henningsen & Meinck, 2003) and 72.7% (Engberg et al, 2017) with a pooled prevalence of 46.1% (95% CI 35.8-56.8%) across 10 studies. The model showed significant heterogeneity (I 2 = 90%, p < 0.0001).…”
Section: Frequency Of Affective Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, no conclusions can be drawn about the specific cause (mental, physical, and/or social health) that contributed to the participants’ ratings. However, it is known that individuals with DSD more often have mental health problems than the normal population [ 46 , 47 ]. This fact was also seen in a previously conducted analysis concerning the mental health of this study population [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies (22,(36)(37)(38)(39) we performed a retrospective case-control study to estimate the risk of neurodevelopmental and psychiatric disorders in individuals with TS. Odds ratios (OR) for each neurodevelopmental and psychiatric outcome were estimated from conditional logistic regression models and were strati ed on matched sets to account for matching by year and county of birth.…”
Section: :4 Statistical Analysesmentioning
confidence: 99%